DINAMIKA PERAN IBU DALAM MENDIDIKAN ANAK - Sulis Rokhmawanto (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Abstract: Family is the first place and uyama in mendidika child, thus delivering his son to success in the future. The demands of the times make a change in the pattern of economy and changes in understanding of the essence of the family in the education of their children. The gathering does not gather from the meal, it becomes the legitimacy of a father to work to leave the family and his duty to educate his son, so the obligation to educate the child is bestowed on the mother. In the process of education of children in the family of a mother experiencing dynamics, namely social dynamics, psychology, and also the dynamics of educational content of his children. Abstract: Family is the first place and uyama in mendidika child, thus delivering his son to success in the future. The demands of the times make a change in the pattern of economy and changes in understanding of the essence of the family in the education of their children. The gathering does not gather from the meal, it becomes the legitimacy of a father to work to leave the family and his duty to educate his son, so the obligation to educate the child is bestowed on the mother. In the process of education of children in the family of a mother experiencing dynamics, namely social dynamics, psychology, and also the dynamics of educational content of his children.